Persistence of fortune: Accounting for population movements, there was no post-columbian reversal - Areendam Chanda; C. Justin Cook; Louis Putterman (Brown University, Department of Economics, 2013)
We revisit the idea that colonized countries that were more (less) economically advanced in 1500 became poorer (richer, respectively) by the late 20th century. Using data on place of origin of today's country populations and the urbanization and population density measures used by Acemoglu et al. (2002) as indicators of level of development in 1500, we confirm a reversal of fortune for territories but find persistence of fortune for people and their descendants. The results are equally strong or stronger for three alternative measures of early development, namely years since transition to agriculture, state history, and the Comin et al. (2010) year 1500 technology index. They are also robust to changing end years, to inclusion of non-colonized countries or exclusion of "neo-Europas" and city states, and to the addition of various controls.
Keywords: O40; O10; N10; 330; Long-Run Economic Growth; Comparative Developement; Colonized Countries; Early Developement